Early abduction treatment versus observation in Barlow-positive and mildly unstable hips - Vilma Lankinen; Mika Helminen; Karim Bakti; Jarmo Välipakka; Hannele Laivuori; Anna Hyvärinen (BMC Pediatrics)
Abstract Background In the treatment of DDH, stable but dysplastic hips are safe to observe, and these children do not usually need abduction treatment. It has been reported, that also clinically unstable hips have good spontaneous recovery potential, but only a few studies have investigated the observation strategy in clinically mildly unstable (Barlow positive) hips. A conclusion on the safe treatment strategy for these children has not been made. Materials and methods All early diagnosed mildly unstable (Ortolani negative) hips treated in Tampere University Hospital in 1998–2018 were found, and data was retrospectively collected from the medical records. A total of 510 children were found. There were 222 children with Barlow-positive hips of which 45% were first observed, and 288 children with reported clinically mild hip instability but no reported Barlow-positivity of which 90% were first observed. All the analyses were done separately for these two groups of children. Results Girls were more likely to need abduction treatment after observation in Barlow-positive and mildly unstable groups. There were no differences in the six-month alpha angle or treatment failure rates between early-treated and first-observed children in either of the study groups. Duration of the treatment was not increased in observed children in either of the study groups. Conclusion Observation for about a month in clinically mildly unstable hips with or without Barlow positive signs seems safe regarding the recovery of alpha angles, treatment duration and treatment failures. More research is needed for longer observation times.